Analysis of The Factors Influencing Tourists’ Decisions To Stay In Homestays in The Tanah Datar Regency Area - Salsabilla Wilda Alifia; Retnaningtyas Susanti (Siber Journal of Advanced Multidisciplinary, 2026)
This study aims to identify and analyze the factors influencing tourists’ decisions to stay in homestays in Tanah Datar Regency. The research employed a qualitative research design. The data sources consisted of primary data obtained directly from homestay owners or managers, tourists who had stayed in homestays, and the Department of Tourism, Youth, and Sports of Tanah Datar Regency. The results of the analysis indicate that tourists’ decisions to stay in Tanah Datar Regency are influenced by a combination of several factors, namely price, location, facilities, service quality, and the attractiveness of the tourist destination. The findings also show that tourists’ decisions to stay in Tanah Datar Regency are influenced by the integration of accommodation quality and destination quality. Competitive pricing, strategic locations, adequate facilities, and good service have been able to provide satisfaction to tourists. However, to increase the number of tourists staying overnight and to extend their length of stay, the local government, together with tourism business operators, needs to develop new tourist attractions, organize more cultural activities and events, improve digital promotion, enhance accessibility, and raise homestay management standards so that Tanah Datar Regency becomes a destination that is not only attractive to visit but also appealing as a place to stay for a longer period.